A survival guide for culinary professionals - Gelb, Alan; Levine, Karen (Clifton Park, NJ, 2005)
A survival guide which is lively and easy-to-read, full of anecdotes and useful information for the busy student or professional. With tips from culinary professionals on everything from organizaiton to stress management to owning your own restaurant, this is one book busy students and professionals won't want to be without.
Keywords: Cooking; Cuisine